Right Lung Agenesis; Isolated and with Accompanied Anomalies - Yakup Canıtez; Şükrü Çekiç; Arif Gürpınar; Nihat Sapan (Güncel Pediatri)
Right lung agenesis is a rare anomaly that can be isolated or accompanied by system anomalies such as cardiac, skeletal or urinary systems. Case 1, a four-month-old girl, was brought because of respiratory distress. Patient had polydactyly, syndactyly of right thumb, right mandibular hypoplasia and low-set dysmorphic ears. Lung x-ray and thorax computerized tomography (CT) were consistent with right pulmonary agenesis and butterfly vertebra was evident in the 7th thoracic level. Thoracic CT angiography revealed narrowing of the left main bronchus and esophagus due to compression of aorta, left pulmonary artery and right atrium. In bronchoscopy, narrowing due to compression at the carina level was seen and right main bronchus was not seen. In abdominal ultrasonography, right kidney placement anomaly (pelvic ectopia) was present and renal scintigraphy revealed fusion in both kidneys. With these findings, it was found that right pulmonary agenesis was accompanied by ipsilateral radial ray anomaly, renal anomaly, vertebral anomaly and hemifacial microsomia. Case 2, a fifteen-year-old male patient, was diagnosed as pulmonary agenesis via chest x-ray, pulmonary CT and bronchoscopy after a wheezing episode when he was 2 months old. Patient had no complaint except for exhaustion that is aggravated by exercise during last year. In physical examination, he had a mild scoliosis toward right, respiratory sounds were diminished on right hemithorax and heart sounds were heard on right side. Chest x-ray and thoracic CT were consistent with right lung agenesis. No abnormality was found in echocardiography and abdominal ultrasonography was normal. Accompanied cardiovascular anomalies, distortions of intrathoracic structures and recurrent infections are main factors that affect mortality and morbidity. Here, two cases with right lung agenesis, isolated and accompanied by multiple anomalies, were presented. (Journal of Current Pediatrics 2013; 11: 134-7)